A reação da Igreja Presbiteriana do Brasil ao advento do pentecostalismo em Pernambuco (1920-1930) - Souza, José Roberto de (2013)
Our research aims at analyzing the reaction of the Presbyterian Church of Brazil against the implementation of the Pentecostal Movement in Pernambuco in the 1920s. We seek to trace the activities of the early Presbyterian Churches and of the Assembly of God in this State from the examination of the press both Pentecostal and Presbyterian as well as the Pernambuco Presbytery minutes, the agency that coordinated the work of the Presbyterian Church of Brazil in Pernambuco. These sources have helped us understand the differences and indifferences between both groups that led these churches; we have seen also the arguments and strategies implemented by the Presbyterian Church of Brazil (IPB) as it took a stand against the Pentecostals of the Assembly of God. Moreover, we analyzed the characteristics and doctrinal differences with respect to the reaction on the Presbyterians part against a movement comprised by immigrants, negroes and women, that is, a religion of marginalized people.